Analysis of Finnish young soccer player`s passing and dribbling skills in 2002-2010 - Vanttinen, T. (7th World Congress on Science and Football (WCSF), 2011, 2011)
One of the most important variables for measuring performance in youth soccer is technical performance [1] because prerequisite for young players to progress is that they possess a certain level of technical skill [2]. The aim of this study was to examine Finnish young soccer players` passing and dribbling skills from year 2000 to 2010. Methods The passing and dribbling tests [3] were analyzed from annually organized youth soccer skill championships from 2002 to 2010. The subjects who were qualified from regional competitions to championships competed in six age categories from 10 to 15y in both gender (n=1708). Test results were analyzed in both gender in a 6 x 9 (age group x year) and gender difference in a 2 x 6 (sex x age group) analysis of variance. Relative development by age and gender in both tests are presented in Table 1. Results In passing test, a significant main effect for age (F5,921=93.78***) and year (F8,921=2.74**) was found in boys and for age (F5,679=95.82***), year (F8,679=5.13***) and age x year (F40,679=1.53*) in girls. Between gender, a significant main effect was found for sex (F1,1696=617.55***), age (F5,1696=186.06***) and sex x age (F1,1696=4.47***). In dribbling test, a significant main effect for age (F5,921=97.27***) and year (F8,921=3.88***) was found in boys and for age (F5,679=81.30***), year (F8,679=3.62***) and age x year (F40,679=1.48*) in girls. Between gender, a significant main effect was found for sex (F1,1696=1014.55***), age (F5,1696=181.35***) and sex x age (F1,1696=8.22***). Conclusion Performance in passing and dribbling tests improved with age from 10 to 14y in both gender and boys were better than girls in all age categories. An adolescent acceleration in the skill test results could be noticed between 12 to 13y in girls and between 13-14y in boys. It was also found that the skill level was not constant across examined time period 2002 - 2010 even though only the most skilful players were examined each year.